Error Analysis In Academic Writing: Challenges In Writing Thesis Abstracts Among Sharia Economics Students - Noviarini, Tiara (Jurnal Ilmu Sosial Mamangan, 2025)
This study investigates the grammatical errors in thesis abstracts written by Sharia Economics students, focusing on the types and frequency of errors. Employing a descriptive qualitative approach, the research categorizes errors into omission, addition, misformation, and misordering. Data analysis reveals that omission errors are the most frequent, followed by misformation, addition, and misordering. These findings indicate that students struggle with academic writing due to limited grammar proficiency and challenges in structuring scholarly texts. The study highlights the necessity of targeted interventions, such as specialized writing programs, enhanced supervision, and systematic feedback, to improve students' academic writing skills.